The role of agency theory in the relationship between foreign ownership and performance-risk of stock in Indonesia: is one or two-way interaction? - Ahmad Maulin Naufa; I Wayan Nuka Lantara (Diponegoro International Journal of Business, 2018)
Using agency theory as a theoretical basis, this paper aims to examine the relationship between foreign ownership, performance, and risk. Particularly, we examine whether the foreign ownership can improve or reduce the performance and risk. Vice versa, it also examine whether performance and risk may also influence the foreign ownership of stock. We utilized samples from the 100 Kompas Index from the Indonesian Stock Exchange (IDX), and we obtained 87 stocks from 2011-2017. We analyzed the relationship using ordinary least square by EViews 10.0. The result shows that the foreign ownership contributes positively to the improvement of performance, although the performance does not affect significantly to foreign ownership. Then, the relationship between the foreign ownership and the risk are not significant. The relationship the risk to the foreign is also not significant. To commence with, the foreign has an essential role in the improvement of Indonesian stock performance.